Scheme of Government Policy in Accelerating COVID-19 Vaccination for Elderly Groups in Indonesia - Vayed, Dodi Al; Suswanta, Suswanta; Istiqoh, Akhdiva Elfi (Jurnal Kebijakan Kesehatan Indonesia, 2025)
COVID-19 vaccination must be given to the elderly group (> 60 years) because it is at high risk of being infected with COVID-19 with a high mortality rate. This study aims to analyze the implementation of government policies in reducing the spread of COVID-19 through accelerating vaccines for the elderly ( elderly) in Indonesia, and this study used a qualitative research method. The data sources for this research were online news media and the Nvivo 12 plus application as software for data analysis. The results of the study showed that the factors causing the slow process of vaccination for the elderly were lack of socialization regarding COVID-19 vaccination, hoax news related to vaccination, limited access to vaccine services, and comorbidities or comorbidities for the elderly. Vaccination for the elderly group was carried out by classification. Tasks through the central Government were then handed over to the provincial Governor and district and city governments, according to the bureaucratic structure such as the UPTD puskesmas in every region in Indonesia.